Recovery of inter-row shading losses using differential power-processing submodule DC–DC converters. (October 2016) - Doubleday, Kate; Choi, Beomseok; Maksimovic, Dragan; Deline, Chris; Olalla, Carlos
Highlights: Tightly-packed solar arrays are found to have significant inter-row shading loss. A higher density of modules makes increased production from rooftop systems more economic. Embedded sub-module power electronics can confer a 7% increase in annual energy output. Diffuse irradiance losses can limit the recoverable power from distributed electronics. Abstract: Large commercial photovoltaic (PV) systems can experience regular and predictable energy loss due to both inter-row shading and reduced diffuse irradiance in tightly spaced arrays. This paper investigates the advantages of replacing bypass diodes with submodule-integrated DC–DC converters (subMICs) to mitigate these losses. Yearly simulations of commercial-scale PV systems were conducted considering a range of row-to-row pitches. In the limit case of array spacing (unity ground coverage), subMICs can confer a 7% increase in annual energy output and peak energy density (kW h/m 2 ). Simulation results are based on efficiency assumptions experimentally confirmed by prototype submodule differential power-processing converters.